Preparation of Cu-Graphene Composite Thin Foils via DC Electro-Deposition and Its Optimal Conditions for Highest Properties. Issue 9 (1st January 2017) - Song, Gongsheng; Yang, Yanpeng; Fu, Qiang; Pan, Chunxu
Abstract : In this paper, the copper (Cu)-graphene (Gr) composite thin foils with a thickness around 20 μm were prepared by means of a direct current (DC) electro-deposition method. The effect of three vital factors, i.e., graphene oxide (GO) concentration in the electrolyte, applied current density and bath temperature on the microstructural variations and mechanical properties of the composite thin foils was investigated in detail. The experimental results revealed that: 1) with increasing GO concentration, the microstructures or grains of the composite thin foils varied from needle-like → compact grains → large triangle cone. The optimal value was 0.5 g/L. 2) At the 0.5 g/L GO concentration, the higher the current density was applied, the smaller the grain size of the foils was observed until a critical point (10 A/dm 2 ), and then kept unchanged essentially. The graphene distributions within the foils were relatively uniform except for aggregations under high current density (20 A/dm 2 ). 3) The high temperature leaded to large grain size and more Gr aggregations. 4) According to the tests of mechanical properties, the optimized processing conditions were as follows, 0.5 g/L GO concentration, 10–20 A/dm 2 applied current density and 25–40°C temperature. The influencing mechanisms of the factors were also discussed.